The Impact of Climate Change on Food Inflation: The Mediating Role of Trade and Monetary Policies - A System GMM Analysis of 34 African Countries - Saou, Mohamed; Namri, Taha; El Abbassi, Idriss (International Journal of Energy Economics and Policy, 2025)
This article examines the impact of climate change (CC) on food inflation using a sample of 34 African countries from 2001 to 2022, employing the System Generalized Method of Moments (System GMM) estimators. The results show that high temperatures significantly contribute to the increase in food inflation, whereas precipitation has a positive but statistically insignificant effect. A second objective of this study is to introduce the moderating role of trade and monetary policies in addressing food inflation under climatic conditions (high temperatures). The findings indicate that a trade policy promoting food imports can mitigate the climate impact on food inflation, while a monetary policy directing credit toward the agricultural sector tends to amplify the climate effect on food inflation. Our results emphasize the crucial importance of monetary policies focused on sustainability objectives and CO2 emission reduction.